ChemInform Abstract: β‐Glucuronidase‐Responsive Prodrugs for Selective Cancer Chemotherapy: An Update. Issue 19 (13th May 2014) - Tranoy‐Opalinski, Isabelle; Legigan, Thibaut; Barat, Romain; Clarhaut, Jonathan; Thomas, Mikael; Renoux, Brigitte; Papot, Sebastien
Abstract Review: 136 refs.